Paradigma Pengembangan Kurikulum: Analisis Prinsip, Model Desain, dan Pendekatan Implementatif dalam Perspektif Teoretis dan Praktis - Mardiati M; Juhariati Juhariati; Dadang Sumarna (Jurnal Sultra Elementary School, 2026)
Curriculum development is a fundamental process in determining the direction, content, and learning strategies in the education system. This literature study aims to analyze the paradigm of curriculum development through a review of principles, design models, and implementation approaches from theoretical and practical perspectives. The curriculum is not only understood as a formal document, but also as a dynamic system influenced by social change, student needs, and scientific developments. This research uses a literature study method by examining various relevant scientific sources, such as journals, books, and current education policies. The results of the study indicate that the principles of curriculum development include relevance, flexibility, continuity, effectiveness, and efficiency, which form the basis for formulating curriculum content. Widely used curriculum design models include the Tyler model, Taba model, and competency-based models that emphasize learning outcomes. Meanwhile, implementation approaches in curriculum development include academic, humanistic, social reconstruction, and technological approaches, each of which has a different orientation in the learning process. Theoretically, curriculum development is understood as a systematic and rational process, while in practice it emphasizes adaptation to the school context and student needs. These findings indicate that the integration of principles, models, and approaches is crucial for producing a responsive, adaptive, and sustainable curriculum to meet the challenges of 21st-century education.